Application of dye-sensitized solar cell (DSSC) from polyurethane (PU)/diol-nai electrolyte with activated carbon (AC) composite electrode / Mohd Hamizan Selamat and Azizah Hanom Ahmad - Selamat, Mohd Hamizan; Ahmad, Azizah Hanom (2017)
Application of dye-sensitized photoelectrochemical cell (DSSC) was developed using bio-based hybrid polyurethane (PU) polymer and composite electrolyte of Sodium iodide as cation of charge transport. The conducting electron transport material for the regenerative mechanism for Redox couple (I-1/I-3) was due corrosion in contacts of electrode. The polymer as additive has leveraged conductivity level of PU-composite electrolyte prepared by varying amount of Sodium iodide (NaI) via solution casting technique. These properties of composite electrolyte exhibited photoelectrochemical cell that was least corrosive (Block Membrane) for bio-based polymer electrolyte. DSSC design of heterojunction cell requires essential need of functions such as light absorption, charge regeneration-separation and transport to electrodes for a complete cell to work. The addition of polymer composite electrolyte in the redox energy separation of electrical transport was effective for bulk material of the DSSC cell system. The electrical conductivity of electrolyte material was evaluated as fair (x10−5S.cm-1) using electrical impedance (EIS) with efficiency performance of photo-electro conversion. The hybrid-dye-sensitized solar cell of PU-Cu/TiO2-dye/PU-NaI-I2/B-AC configuration gave a response under light intensity of 100 mW cm−2 with 3.9% conversion efficiency with current density, Jsc of 0.06 mA cm−2 and open circuit voltage, Voc of 0.14 V respectively.